EFEKTIVITAS MODEL PEMBELAJARAN TALKING STICK DISERTAI PENEMUAN TERBIMBING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI 11 YOGYAKARTA - Retno Wulandari; Istiqomah Istiqomah (Universitas Sarjanawiyata Tamansiswa, 2015)
This research aims at knowing that cooperative learning model type talking stick with discovery learning appoarch is more effective than conventional learning model toward the result of mathematics subject of the students grade VIII SMP Negeri 11 Yogyakarta. This research uses Pretest-Posttest Control Group Design. The research has two variables. The independent variable consists of cooperative learning model type talking stick with discovery learning approach and conventional learning model, and the dependent variable is result of mathematics subject. The population was all students grade VIII in SMP N 11 Yogyakarta consisting of 136 students in 4 classes. The research sample of two classes was taken by cluster random sampling technique. Data collection technique uses pretest and posttest. The data analysis uses t-test, in which it was previously tested using pre-requisite test, namely; normality test and homogenity test, and than compares testimatedÂ with ttable, with df = n1 + n2 -2, and Î± = 5%. If testimated Â Â ttable , then Ho is refused. This means that the average gain score of experiment class is better than the average gain score of control class.Based on the result of estimated gained-score it is known that the value of testimated = 2,351, whereas ttable = 1,671. Because testimated = 2,351 > ttable = 1,671, then Ho is refused. This means that the average gain score of experiment class is better than the average gain score of control class. Therefore, it can be concluded that cooperative learning model type talking stick with discovery learning appoarch is more effective than conventional learning model toward result of math subject of the students grade VIII SMP Negeri 11 Yogyakarta.